Episodic and Semantic Memory Contribute to Familiar and Novel Episodic Future Thinking - Wang, Tong; Yue, Tong; Huang, Xi Ting (Frontiers in Psychology, 2016)
Abstract Increasing evidence indicates that episodic future thinking (EFT) relies on both episodic and semantic memory; however, event familiarity may importantly affect the extent to which episodic and semantic memory contribute to EFT. To test this possibility, two behavioral experiments were conducted. In Experiment 1, we directly compared the proportion of episodic and semantic memory used in an EFT task. The results indicated that more episodic memory was used when imagining familiar future events compared with novel future events. Conversely, significantly more semantic memory was used when imagining novel events compared with familiar events. Experiment 2 aimed to verify the results of Experiment 1. In Experiment 2, we found that familiarity moderated the effect of priming the episodic memory system on EFT; particularly, it increased the time required to construct a standard familiar episodic future event, but did not significantly affect novel episodic event reaction time. Collectively, these findings support the hypothesis that event familiarity importantly moderates episodic and semantic memory’s contribution to EFT.